Эффективность лечения больных химиорезистентным туберкулезом легких при наличии полостей распада в s6 легких и сопутствующей эндобронхиальной патологии с использованием в комплексном лечении изониазид-гидроксиметилхиноксалиндиоксида - Разнатовская, Е. Н.; Разнатовська, Олена Миколаївна; Raznatovska, O. M. (My University, 2015)
Повышение эффективности лечения больных химиорезистентным туберкулезом легких при наличии полостей распада в S6 легких и сопутствующей эндобронхиальной патологии. Цель исследования: изучение эффективности лечения больных химиорезистентным туберкулезом легких при наличии полостей распада в S6 легких и сопутствующей эндобронхиальной патологии с использованием в комплексном лечении изониазид-гидроксиметилхиноксалиндиоксида. Підвищення ефективності лікування хворих на хіміорезистентний туберкульоз легень при наявності порожнин розпаду в S6 легень і супутньої ендобронхіальної патології. Мета дослідження: вивчення ефективності лікування хворих на хіміорезистентний туберкульоз легень при наявності порожнин розпаду в S6 легень і супутньої ендобронхіальної патології з використанням у комплексному лікуванні ізоніазид-гідроксиметилхіноксаліндіоксиду. Improving the efficiency of treatment of patients with drug-resistant pulmonary tuberculosis in cases of cavitation in the S6 of lungs and concomitant endobronchial pathology. Objective of the study: to examine the effectiveness of treatment of patients with drug-resistant pulmonary tuberculosis in cavitation of the S6 of lungs associated with endobronchial pathology using isoniazid-hydroxymethylquinoxalinedioxyde in comprehensive treatment.
Ефективність лікування хворих на хіміорезистентний туберкульоз легень при наявності порожнин розпаду в s6 легень і супутньої ендобронхіальної патології з використанням в комплексному лікуванні ізоніазид-гідроксиметилхіноксаліндіоксиду
Treatment success in patients with drug-resistant pulmonary tuberculosis in cavitation of s6 of lungs and concomitant endobronchial pathology using isoniazid-hydroxymethylquinoxalinedioxyde in the comprehensive treatment
Keywords: химиорезистентный туберкулез легких; полости распада в S6 легких; эндобронхиальная патология; лечение; drug-resistant pulmonary tuberculosis; cavitation in S6 of lungs; endobronchial pathology; treatment; хіміорезистентний туберкульоз легень; порожнини розпаду в S6 легені; ендобронхіальна патологія; лікування